ANALISIS STRATEGI PEMASARAN SYARIAH DALAM MENINGKATKAN OMSET PENJUALAN PADA USAHA IWA-QU DI KOTA JAMBI - Zunita Putri Handayani; Ahsan Putra Hafiz (ICONS: Islamic Economics Journal, 2025)
Product quality is one of the factors considered by consumers in meeting their needs and in considering purchasing decisions. So that in increasing sales turnover in the Iwa-qu business, quality productsare needed. High-quality products and affordable prices will attract public interest so that it can be said that the sharia marketing strategy carried out by the Iwa-qu business is successful. The purpose of this study is to analyze the sharia marketing strategy carried out by the Iwa-qu business in increasing its sales turnover. This study uses a qualitative method, by means of interviews and documentation to produce the required data. Interviews were conducted with sources, namely the owner/leader of the Iwa-qu business in Jambi City, the production team and involving several consumers to assess the quality of the products from the Iwa-qu business. The results of the study indicate that there is a relationship between the sharia marketing strategy carried out by Iwa-qu and increasing sales turnover. By maintaining product quality, it can attract consumer interest and consumer satisfaction so that the marketing strategy carried out by Iwa-qu can be said to be successful and can increase sales turnover.